OXYTOCIN IMPLICATION FOR SCHIZOPHRENIA FUTURE TREATMENT - Asmy, Hatimul (Journal of Psychiatry Psychology and Behavioral Research, 2025)
Introduction: Schizophrenia is a mental disorder, manifested as positive symptoms, negative symptoms, and cognitive dysfunction. Antipsychotic medication is given to treat schizophrenia; however, recently, antipsychotic medication is less effective in improving negative symptoms and cognitive deficits. Several neurotransmitters and neuropeptides are believed to be involved in the mechanism of schizophrenia, one of which is oxytocin. Methods: The author uses the literature review method with international journals limited to the period from 2014 to 2024 that discuss oxytocin as a treatment in schizophrenia patients. Results: Several results of studies showed that schizophrenia therapy using oxytocin improved negative symptoms and cognitive function in schizophrenia patients. These studies are based on previous research, which showed lower concentrations of oxytocin in schizophrenia patients. Discuss: Oxytocin acts as a human behavior regulator, and the oxytocinergic system is involved in the emergence of schizophrenia symptoms. Oxytocin administration through intranasal is chosen to deliver oxytocin because it reaches the central nervous system more easily. Oxytocin administration can improve oxytocin concentration in cerebrospinal fluid. Increasing oxytocin levels is significant in improving negative symptoms and cognitive function in schizophrenia patients. Conclusion: Oxytocin administration intranasally can increase oxytocin concentration to improve negative symptoms and cognitive function in schizophrenia patients.